Establishing a Multidisciplinary Network for the Workup of Sudden Cardiac Death. Issue 2 (June 2015) - Duncanson, Emily R.; Lynch, Kate; Baker, Andrew M.; Abdelhadi, Raed H.; Mackey-Bojack, Shannon M.
Sudden cardiac death (SCD) often falls under the jurisdiction of the medical examiner (ME). A recent expert consensus statement recommends cardiac evaluation for all first degree blood relatives of an individual with SCD and supports the referral of these family members to a multidisciplinary inherited arrhythmia clinic; however, most MEs lack the appropriate clinical network for a specific referral and family members are often not followed up. In 2010, Minnesota MEs and cardiovascular pathologists began collaborating with a cardiology referral center specializing in familial cardiac conditions to form a regional Sudden Death Network (SDN). The cardiac pathologists and MEs have established protocols for appropriate specimen retention in accordance with the National Association of Medical Examiners position paper on postmortem deoxyribonucleic acid (DNA) collection and for referring families for clinical evaluation. The expertise of a genetic counselor has been essential to the evaluation of these families in coordinating appropriate genetic testing and assisting with the identification of at-risk family members in extended pedigrees. This SDN uses a multidisciplinary approach for referral of family members for screening and treatment of SCD risk and represents an important resource for MEs. Development of SDNs across the country would lead to a more uniform approach to SCD follow-up and a more efficient use of clinical resources. The ME's role is essential in consulting cardiac pathologists when needed, establishing the correct diagnosis, collecting and retaining appropriate specimens, and initiating the referral of at-risk family members to specialists.